Diagnostic Value of Urinary Dysmorphic Erythrocytes in SLE Patients with Three Different Methods - Ersa Bayung Maulidan; Ferdy Royland Marpaung (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Systemic Lupus Erythematosus (SLE) is an autoimmune disease with various clinical manifestations. Lupus nephritis isthe most common severe manifestation with a poor prognosis. Hematuria is included in the Lupus Activity Criteria Count(LACC) and SLE Disease Activity Index (SLEDAI). Phase Contrast Microscope (PCM) availability as a recommended instrumentfor dysmorphic erythrocytes evaluation is exclusive, thus causing this examination to be performed rarely. This study aimedto investigate the diagnostic value of dysmorphic erythrocytes in SLE patients with hematuria using Low Condenser LightMicroscope (LCLM), PCM, and UF-500i. This research was a cross-sectional study with consecutive sampling; 58 fresh urinesamples were examined with UF-500i during May-July 2019. Percentage of dysmorphic erythrocytes were evaluated usingLCLM and PCM. Difference percentages of dysmorphic erythrocytes were analyzed using the Wilcoxon Signed Ranks test,degree of agreement by Kappa coefficient, cut-off, sensitivity, and specificity by ROC curve. Dysmorphic erythrocytepercentage in LCLM and PCM showed a significant difference (p < 0.001) and a low degree of agreement (Kappa=0.373).Dysmorphic erythrocyte cut-off with LCLM was 7.5% (sensitivity 70%, specificity 68%) and PCM was 6.5% (sensitivity 74%,specificity 65%). Dysmorphic? flagging from UF-500i showed a sensitivity, specificity, PPV, NPV of 78%, 52%, 58% and 73%,respectively. LCLM can be considered a substitute for PCM for evaluating dysmorphic erythrocytes with its cut-off, so theclinician will be more alert to abnormalities that cause hematuria. Further research with larger samples and definitediagnosis with a kidney biopsy is needed to obtain more accurate results.